Antiplatelets and Anticoagulants in Dermatological Surgery. A Protocol for Clinical Practice - Leão, Diana (2021)
The increasing number of patients undergoing antithrombotic therapy and a higher prevalence of skin neoplasia implies an adequate management of these drugs in the perioperative period during dermatological surgery. The authors present and discuss the protocol for clinical practice followed in the Dermatology and Venereology Department of Centro Hospitalar Universitário São João. Suspension or maintenance of therapy with antiplatelet and/or anticoagulant drugs should be assessed individually, taking into account the patient and intervention’s bleeding risk and the degree of thrombotic risk of the patient. In these patients, local hemostatic measures are particularly relevant in the management of perioperative haemorrhage and should be thorough. The Immunohemotherapy Department provides collaboration in situations of difficult bleeding management.